Dampak Teknologi Informasi dan Komunikasi, Belanja Modal, dan Produktivitas Tenaga Kerja Terhadap Pertumbuhan Ekonomi di Indonesia - Al Ikhsan, M. David; Usman, Moneyzar; Ananta, Prayudha (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
Economic growth has an important role as the main means of improving the welfare of the Indonesian people. However, Indonesia faces challenges in economic growth due to uneven economic growth factors in each province. This study aims to analyze the effect of IP-ICT, capital expenditure, and labor productivity as well as the effect of the covid-19 pandemic on economic growth in Indonesia in 2017-2022. The data used in this study is quantitative panel data with a sample population of 34 provinces in Indonesia. The research method uses multiple linear regression analysis with the Fixed Effect Model (FEM) as the best model. The regression results show that IP-ICT and labor productivity have a significant positive effect, while capital expenditure has no real impact, and the covid-19 dummy has a significant effect on economic growth in Indonesia in 2017-2022.